Legal Protection for Human Trafficking Victim, Especially Women and Children in West Kalimantan - Yenny AS; Nurfitriawati Nurfitriawati; Klara Dawi; Sri Ayu Septinawati (International Journal of Multi Discipline Science, 2018)
West Kalimantan Province, as one of provinces in Indonesia which has specific geographical condition is bordering with East Malaysia through official Cross-Border Post between Entikong and Tebedu, Badau and Lubuk Antu, Aruk and Biawak, and no less than fifty path ways (not official) can be passed to get in and get out to and from East Malaysia region. This geographical encouraged trafficking improvement to abroad with various modes. In fact, trafficking was affected by many factors, including stigma, poverty, lack of education, family resilience, and other factors, where women and children are the victim. The aim of this research to reveal how is the legal protection for the victim. Although there were many studies had been done about it, but the focus of this research is the obstacles face to give legal protection for the victims of trafficking in West Kalimantan border, where the top of the problem is victims role, sometimes they don’t realize that they are the victims, so legal protection effort as stipulated in Trafficking Rules was not optimal. Through socio-legal research found an interesting thing, the lack of victim realized they were victims who have to get legal protection, so complicated a legal assistant for legal effort. Beside of that, trafficking as transnational crime and organized, it is complicated for legal enforcement, because of trafficking perpetrators are in the state border cross. The abstract contains: research objectives, implementation methods, analysis techniques and activity results. Typed with font Times New Roman letter 11, single space, and italicized.